2011
DOI: 10.1111/j.1365-2133.2011.10267.x
|View full text |Cite
|
Sign up to set email alerts
|

BRM and BRG1 subunits of the SWI/SNF chromatin remodelling complex are downregulated upon progression of benign skin lesions into invasive tumours

Abstract: Background  Nonmelanoma skin cancer is caused by exposure to ultraviolet radiation within sunlight. Actinic keratoses (AKs) are benign precursor lesions that can develop into invasive squamous cell carcinoma (SCC). Little is known about the molecular events that lead to human skin cancer progression from benign to invasive. Objectives  To determine novel genes that may be involved in skin cancer progression based on data from an initial microarray screen of human skin cancers. Methods  The SWI/SNF chromatin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…67 A subsequent study reported that expression of BRM and BRG1 proteins was reduced approximately 10-fold in 100% of SCC (n = 11) and BCC (n = 5) specimens, but not in AK (n = 11) samples, which were similar to normal-appearing skin (n = 9). 68 These data suggest that loss of BRM and BRG1 expression is a late and necessary event in the progression of nonmelanoma skin cancer. 68 SUMMARY Environmental exposures to UVradiation initiate a multifactorial cascade of molecular, cellular, viral, immune, and genetic events that influence the progression of AK to malignancy.…”
Section: Human Papillomavirusmentioning
confidence: 96%
See 1 more Smart Citation
“…67 A subsequent study reported that expression of BRM and BRG1 proteins was reduced approximately 10-fold in 100% of SCC (n = 11) and BCC (n = 5) specimens, but not in AK (n = 11) samples, which were similar to normal-appearing skin (n = 9). 68 These data suggest that loss of BRM and BRG1 expression is a late and necessary event in the progression of nonmelanoma skin cancer. 68 SUMMARY Environmental exposures to UVradiation initiate a multifactorial cascade of molecular, cellular, viral, immune, and genetic events that influence the progression of AK to malignancy.…”
Section: Human Papillomavirusmentioning
confidence: 96%
“…68 These data suggest that loss of BRM and BRG1 expression is a late and necessary event in the progression of nonmelanoma skin cancer. 68 SUMMARY Environmental exposures to UVradiation initiate a multifactorial cascade of molecular, cellular, viral, immune, and genetic events that influence the progression of AK to malignancy. Although particular alterations in gene expression are strongly associated with invasive SCC, there is no mechanism to predict which AKs are at increased risk for malignant progression to invasive SCC.…”
Section: Human Papillomavirusmentioning
confidence: 96%
“…At least haploinsufficiency of BRG1 is recognized [25][26][27]62], while further studies are necessary whether such a role exists for STK11/LKB1 or not. Similar to BRG1, abnormalities of BRM in various cancers have been reported [58][59][60][61][63][64][65][66][67][68][69]. Though the early studies of cell lines and animal models strongly suggested subunits of SWI/SNF proteins as tumor suppressor, the first definitive evidence that members of these complexes function as tumor suppressive was shown by Versteege and colleagues.…”
Section: Roles Of Swi/snf Proteins In Cancermentioning
confidence: 95%
“…Some of the studies included genetic analysis of STK11/LKB1 and showed mutation in a subset of tumors especially related with Peutz-Jeugher Syndrome such as breast, colorectal, lung, pancreatic, biliary and ovarian cancer [41][42][43][44][45][46][47][48][49]. On the other hand, quite a lot of studies reported mutations and/or loss or various alterations of BRG1 in human cancer lines and primary tumors [50][51][52][53][54][55][56][57][58][59][60][61]. Thus genes at this chromosomal locus may involve in various type cancer exclusively or in cooperation in some cancer types.…”
Section: Roles Of Swi/snf Proteins In Cancermentioning
confidence: 99%
“…Studien, in denen nach BRM-Mutationen in primären Hauttumoren gesucht wurde, haben beim SCC und beim BCC eine Hotspot-Mutation identifiziert, deren Ursache UV-A-Strahlen sein könnten [8]. Die Untersuchung der BRM-und BRG-1-Proteine hat den Verlust der beiden Proteine beim SCC, nicht aber bei AK ergeben, was darauf hindeutet, dass Mutationen in diesem Gen erst in einem späteren Stadium der Progression von AK zum SCC auftreten [9]. Untersuchungen an gentechnisch veränderten Mäusen haben bestätigt, dass die Depletion von BRM den Schutz der Haut vor Photokarzinogenese abschwächt [10].…”
Section: Uv-induzierte Genmutationen Die Zu Aktinischer Keratose Undunclassified